A model of car ownership and use incorporating quality choice and ownership of multiple cars - Jan Rouwendal; John Pommer (European Regional Science Association (ERSA), 2003)
In this paper we develop and estimate a discrete-continuous model for car ownership and use that incorporates quality choice and the decision to own multiple cars. The basic model, used for instance in De Jong (1991), treats all cars as being equal (no differences in quality) and only considers ownership of a single car. In order to introduce quality into the model we assume that the marginal utility of driving is increased by a latent variable (interpreted as quality) that is related to the fixed cost of the automobile, possibly through observable characteristics. We show that this formulation enables us to identify the quality variable. Next, we show how to extend the basic model to situations in which 0,1 or 2 cars can be owned. In order to do this we introduce a sub-utility function for mobility whose value is determined by the kilometers driven by both cars (if two are owned) and is identical to the kilometers driven by the car (if one car is owned). The possibility to substitute the kilometers to be driven by the two cars for each other plays an important role in our formulation. Third, we study the model that results when both extensions are used simultaneously. Our empirical application uses data from the Dutch Consumer Union on (fixed and variable) costs associated with cars. We use an extension of the survey that pays special attention to the ownership of more than one car in the household.
Keywords: 330